52nd Aerospace Sciences Meeting 2014
DOI: 10.2514/6.2014-1280
|View full text |Cite
|
Sign up to set email alerts
|

Stereo PIV Measurements of Low-Aspect-Ratio Low-Reynolds-Number Wings with Sinusoidal Leading Edges for Improved Computational Modeling

Abstract: Stereo Particle Image Velocimetry measurements of the flow field around a unity aspect ratio wing with a sinusoidal leading-edge have been carried out at a Reynolds number Re = 140, 000 for two angles of attack, α α α α = 0º and 15º. These measurements are intended to be used for improved computational modeling of the flow employing Detached Eddy Simulations. For this reason, numerical predictions have also been carried out for the mentioned flow cases, using both the "F2-shielded" modeling and the "delayed" m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Delgado et al [112] carried out Stereo Particle Image Velocimetry (SPIV) measurements and numerical simulation on the NASA LS (1)-0417 airfoil at Re 1.4 Â 10 5 . The experimental setup was similar to that of Zhang et al [81].…”
Section: Experimental (Spiv) and Numerical (Rans And Ddes Comparison)mentioning
confidence: 99%
See 1 more Smart Citation
“…Delgado et al [112] carried out Stereo Particle Image Velocimetry (SPIV) measurements and numerical simulation on the NASA LS (1)-0417 airfoil at Re 1.4 Â 10 5 . The experimental setup was similar to that of Zhang et al [81].…”
Section: Experimental (Spiv) and Numerical (Rans And Ddes Comparison)mentioning
confidence: 99%
“…Camara and Sousa [94], Guerreiro and Sousa [111] and Delgado et al [112] carried out experimental (force balance, SPIV) and numerical (LES, DNS, DES and DDES) studies.…”
Section: Nasa Ls (1)-0417 Airfoilmentioning
confidence: 99%
“…A more thorough summary of the flow and geometric conditions of studies performed on tubercled airfoils can be seen in Table 1. 11 NACA 65-(12)10 2.0 × 10 5 , 6 × 10 5 Delgado et al 12 NASA LS(1)-0417 1.4 × 10 5 Karthikeyan et al 13 NACA 4415 1.2 × 10 5 Fernandes et al 14 NACA 2412 2.185 × 10 6 Skillen et al 15 NACA 0021 1.2 × 10 5 Guerreiro and Sousa 16 NASA LS(1)-0417 7.0 × 10 4 , 1.4 × 10 5 Hansen 10 NACA 0021, NACA 65-021 4.37 × 10 3 , 5.25 × 10 3 Hansen et al 17 NACA 65-012 1.2 × 10 5 Johari et al 4 NACA 63 4 -021 1.83 × 10 5 Levshin et al 18 NACA 63 4 -021 1.83 × 10 5…”
Section: Introductionmentioning
confidence: 97%
“…10 In parallel to the experimental efforts, numerical predictions of the flow around the baseline and modified wings have subsequently been performed employing panel methods, 11 Reynolds-Averaged Navier-Stokes (RANS) approaches using different turbulent modelings such as Spalart Allmaras, 12 kε, 13,14 kω0.25emSST, 1517 and RANS transition models such as γReθ. 18 Furthermore, Direct Numerical Simulation (DNS), 19,20 Large Eddy Simulation (LES), 21,22 and hybrid RANS-LES models 2325 have also been utilized to yield a better understanding of the unsteady flow behavior. In a nutshell, all of the previous investigations indicated that the tubercles in the leading edge enabled flow manipulation, eventually delaying the occurrence of stall.…”
Section: Introductionmentioning
confidence: 99%